PEMBINAAN MOTIVASI ATLET DAN PELATIHAN OLAHRAGA TENIS MEJA BAGI SISWA SMA CITRA HARAPAN - Sihotang, Jenas Pardomuan; Nofrizal, Dedi; Saragih, Jepri Hartanta; Tarigan, Jhon Fernando; Gea, Jen Rahmad; Togatorop, Jepni Piola (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2025)
Physical activity can be done by students either individually or in groups. Students can utilize the sports facilities and infrastructure available around them. The availability of adequate sports facilities and infrastructure is very important to increase the enthusiasm and motivation of students in doing sports activities to become their health. The availability of facilities and infrastructure can also provide students with choices to do the sports they want. The availability of sports facilities and infrastructure for Citra Harapan High School students is still very lacking, thus affecting students' interest in doing sports activities. Improving sports facilities and infrastructure by providing table tennis sports facilities and infrastructure is very important for students to increase physical activity. Students are given knowledge about basic techniques in playing table tennis. Some of the techniques provided are service, forehand and backhand.